Dictyostelium discoideum plasma membranes contain an actin-nucleating activity that requires ponticulin, an integral membrane glycoprotein (The Rockefeller University Press, 1990)
In previous equilibrium binding studies, Dictyostelium discoideum plasma membranes have been shown to bind actin and to recruit actin into filaments at the membrane surface. However, little is known about the kinetic pathway(s) through which actin assembles at these, or other, membranes. We have used actin fluorescently labeled with N-(1- pyrenyl)iodoacetamide to examine the kinetics of actin assembly in the presence of D. discoideum plasma membranes. We find that these membranes increase the rate of actin polymerization. The rate of membrane-mediated actin polymerization is linearly dependent on membrane protein concentrations up to 20 micrograms/ml. Nucleation (the association of activated actin monomers into oligomers) appears to be the primary step of polymerization that is accelerated. A sole effect on the initial salt-induced actin conformational change (activation) is ruled out because membranes accelerate the polymerization of pre- activated actin as well as actin activated in the presence of membranes. Elongation of preexisting filaments also is not the major step of polymerization facilitated by membranes since membranes stripped of all peripheral components, including actin, increase the rate of actin assembly to about the same extent as do membranes containing small amounts of endogenous actin. Acceleration of the nucleation step by membranes also is supported by an analysis of the dependence of polymerization lag time on actin concentration. The barbed ends of membrane-induced actin nuclei are not obstructed by the membranes because the barbed end blocking agent, cytochalasin D, reduces the rate of membrane-mediated actin nucleation. Similarly, the pointed ends of the nuclei are not blocked by membranes since the depolymerization rate of gelsolin-capped actin is unchanged in the presence of membranes. These results are consistent with previous observations of lateral interactions between membranes and actin filaments. These results also are consistent with two predictions from a model based on equilibrium binding studies; i.e., that plasma membranes should nucleate actin assembly and that membrane-bound actin nuclei should have both ends free (Schwartz, M. A., and E. J. Luna. 1988. J. Cell Biol. 107:201-209). Integral membrane proteins mediate the actin nucleation activity because activity is eliminated by heat denaturation, treatment with reducing agents, or proteolysis of membranes. Activity also is abolished by solubilization with octylglucoside but is reconstituted upon removal or dilution of the detergent. Ponticulin, the major actin-binding protein in plasma membranes, appears to be necessary for nucleation activity since activity is not reconstituted from detergent extracts depleted of ponticulin.